O princípio constitucional da função social da propriedade privada - Petrucci, Jivago (2007)
The following study aims the social role of private property as a constitutional principle. It does not, therefore, deal with the rules that pertain the social role of property in the several fields (social role of rural or urban estates etc) unless if strongly relevant for the definition of the principle itself. The analysis starts with the study of the constitutional interpretation, a legal type of interpretation which shows peculiarities that demand specific worries from the interpreter. A whole panorama is drawn of the principles of constitutional interpretation, of the distinction between principles and rules and the role of those who work with interpretation. Following, the historical development of the definition of property is examined, since the early days of overwhelming individualism until the recognition of the common objectives of the institute, which allows to define the social role of property, highlighting its relationship with the principle of social justice and the changes that it brings to the traditional definition of property. Finally, this paper analyses the several roles played by the principle of social role of property in our legal system, specially as it regards interpretation, through which the focused principle leads to the interpretation of all the remaining legal rules that compose the national legal system